2021
DOI: 10.3390/ijms22052435
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fusarium verticillioides Fumonisins on Fatty Acids, Sphingolipids, and Oxylipins in Maize Germlings

Abstract: Fusarium verticillioides causes multiple diseases of Zea mays (maize) including ear and seedling rots, contaminates seeds and seed products worldwide with toxic chemicals called fumonisins. The role of fumonisins in disease is unclear because, although they are not required for ear rot, they are required for seedling diseases. Disease symptoms may be due to the ability of fumonisins to inhibit ceramide synthase activity, the expected cause of lipids (fatty acids, oxylipins, and sphingolipids) alteration in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
(69 reference statements)
5
8
0
Order By: Relevance
“…In the present study, free sphingoid bases were more abundant in H21 than in H22 maize samples (Figure 3). This is in agreement with the disruption of CerS by FBs and the subsequent reduction in phytoceramide synthesis in highly contaminated samples, as previously reported by many authors (Zitomer et al, 2008;Dall' Asta et al, 2015;Beccaccioli et al, 2021). In agreement with Beccaccioli et al (2021), we observed an accumulation of S-LCFA in highly contaminated samples, thus confirming the preferential disruption of CerS2 homologs in maize.…”
Section: Sphingolipids and Glycerophospholipidssupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, free sphingoid bases were more abundant in H21 than in H22 maize samples (Figure 3). This is in agreement with the disruption of CerS by FBs and the subsequent reduction in phytoceramide synthesis in highly contaminated samples, as previously reported by many authors (Zitomer et al, 2008;Dall' Asta et al, 2015;Beccaccioli et al, 2021). In agreement with Beccaccioli et al (2021), we observed an accumulation of S-LCFA in highly contaminated samples, thus confirming the preferential disruption of CerS2 homologs in maize.…”
Section: Sphingolipids and Glycerophospholipidssupporting
confidence: 92%
“…It has been recently demonstrated that, among CerS isoforms, maize homologs of CerS2 are preferentially targeted by FBs, increasing therefore the formation of LCFA-sphinganine structures over VLCFA-phytosphingosine ones (Zitomer et al, 2008;Beccaccioli et al, 2021). Very recently, Beccaccioli et al (2021) suggested that FB-driven massive increase in free sphingoid bases and S-LCFA may represent a key signal for controlling programmed cell death in maize infected seedlings.…”
Section: Sphingolipids and Glycerophospholipidsmentioning
confidence: 99%
“…Instrument setting was reported previously (Ludovici et al, 2014). The SIM parameters have been obtained by flow injection of authentic standard and agreed with the literature (Yang et al, 2009;Beccaccioli et al, 2021). FA mass and relative parameters of analysis are reported in Table 2.…”
Section: Fatty Acid Extraction and Hplc-ms/ms Analysismentioning
confidence: 65%
“…acknowledged as a mycotoxin-susceptibility factor (Scala et al, 2014). However, it must be noted that C18:2 and C18:3 derived oxylipins are linked to early FBs accumulation stages as recently reported by several authors (Christensen and Kolomiets, 2011;Dall' Asta et al, 2012;Beccaccioli et al, 2021).…”
Section: Oxylipinsmentioning
confidence: 71%